Passiflora incarnata as an Adjunctive Treatment for Anxiety and Sleep Disorders - Kaźmierczyk, Izabela; Bychowski, Mateusz; Kwaśna, Julia; Załęska, Adrianna; Lenart, Kacper; Górski, Mateusz; Homza, Michał; Zakrzewska, Natalia; Bednarek, Szymon; Kulicka, Joanna (Quality in Sport, 2024)
Background: Passiflora incarnata (commonly known as passionflower) has a longstanding history in ethnopharmacology for its sedative and anxiolytic properties. Recent scientific advancements have expanded its applications, particularly in managing neuropsychiatric disorders such as anxiety, depression, and sleep disturbances. Objective: This review synthesizes current evidence regarding the pharmacological mechanisms, clinical applications, and safety profile of Passiflora incarnata in neuropsychiatric contexts. Methods: A systematic search of peer-reviewed literature from 2016 to 2024 was conducted to assess preclinical and clinical studies investigating the therapeutic potential of Passiflora incarnata. Results: The review identified significant evidence supporting its anxiolytic, sedative, and antidepressant properties, mediated through GABAergic modulation, serotonergic pathways, and other neurochemical mechanisms. Clinical trials demonstrated efficacy in managing perioperative anxiety, sleep disturbances, and benzodiazepine tapering. Its safety profile was favorable, with minimal adverse effects reported. Conclusion: Passiflora incarnata offers a promising herbal alternative or adjunct in the treatment of neuropsychiatric disorders, though further high-quality research is required to standardize its use.